Biochemical screening for aneuploidy in patients with donor oocyte pregnancies compared with autologous pregnancies. (September 2014) - Gupta, Simi; Fox, Nathan S.; Rebarber, Andrei; Saltzman, Daniel H.; Klauser, Chad K.; Roman, Ashley S.
Abstract Objective: The objective was to determine if the rate of abnormal biochemical markers is different in pregnancies conceived by donor oocyte versus those conceived by autologous oocytes. Methods: This is a retrospective cohort study of patients who underwent risk assessment for aneuploidy. Pregnancies conceived by egg donation were matched with control groups who conceived using their own eggs. The primary outcomes were incidence of low PAPP-A or free bHCG in the first trimester or elevated MSAFP, free bHCG or Inhibin A, or low uE3 in the second trimester. Results: 260 singleton gestations were identified who conceived via oocyte donor. There was a significantly higher rate of unexplained elevated MSAFP in pregnancies conceived by egg donation (8% versus 2%, p = 0.028) compared to a control group matched by maternal age. There was also a significantly higher rate of unexplained elevated MSAFP in pregnancies conceived by egg donation (7% versus 2%, p = 0.01) compared to a control group matched by age of the egg donor. Conclusion: Pregnancies conceived by egg donation are more likely to have an unexplained elevation in MSAFP compared to pregnancies not conceived by egg donation regardless of age. Egg donation itself is not associated with other biochemical abnormalities.